Rooted Leadership : seeking God's answers to the eleven core questions every leader faces - Johnson, John E. (Professor of pastoral theology and leadership) (Grand Rapids : Zondervan Reflective, 2022)
"In Rooted Leadership, John E. Johnson explores how Christian theology provides an overarching leadership framework and applies that theory to leadership practices for the sake of equipping credible leaders"--
Includes bibliographical references and indexes.
Keywords: Leadership -- Religious aspects -- Christianity; Leadership